2017
DOI: 10.1017/s0950268817000036
|View full text |Cite
|
Sign up to set email alerts
|

Legionellaprevalence and risk of legionellosis in Japanese households

Abstract: This study determined the occurrence of legionellae in private houses for which there were no available data on aquatic environments other than the water supply system. From June 2013 to November 2014, we collected 138 water and 90 swab samples from aquatic environments in 19 houses. Legionella DNA was detected via a loop-mediated isothermal amplification assay in 66 (47·8%) water and 17 (18·9%) swab samples. High Legionella DNA detection rates were observed in water samples from washing machines and aquariums… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 36 publications
(43 reference statements)
0
20
0
Order By: Relevance
“…1 Flow diagram of the study selection process efficacy of interventions in RCTs and controlled retrospective studies [39,40]. In addition, Cochrane's Q-test and I 2 index were used for determining heterogeneity [41][42][43]. When I 2 index was lower than 50%, the fixed effect model was used and if I 2 index was higher than 50%, the random effect model was utilized [41,[44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Flow diagram of the study selection process efficacy of interventions in RCTs and controlled retrospective studies [39,40]. In addition, Cochrane's Q-test and I 2 index were used for determining heterogeneity [41][42][43]. When I 2 index was lower than 50%, the fixed effect model was used and if I 2 index was higher than 50%, the random effect model was utilized [41,[44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Cochrane's Q-test and I 2 index were used for determining heterogeneity [41][42][43]. When I 2 index was lower than 50%, the fixed effect model was used and if I 2 index was higher than 50%, the random effect model was utilized [41,[44][45][46][47]. Publication bias was detected using Egger's test [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support those from several smaller studies, in which water cultures demonstrated superior sensitivity. [6][7][8] In contrast, another study found that the quantitative yield of Legionella from swabs was greater than water cultures, although qualitative results were not reported. 9 It is theoretically possible that prior swabbing improved the recovery of Legionella from water cultures in this study due to disruption of biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…While the heterogeneity was higher than 50%, the random effect model (REM) was used to estimate the pooled concentration of BTEX in ambient air [ 45 , 48 ].…”
Section: Methodsmentioning
confidence: 99%